Intercomparison of Performance Characteristics of Oslds and TLDs Used For Individual Monitoring - Meye, P.O. (University of Ghana, 2016)
This research work performed an intercomparison on some important performance characteristics of optically stimulated luminescence (OSL) and thermoluminescence (TL) dosimetry systems used by dosimetry services in Gabon and Ghana, respectively. The study verified the status of the selected performance indicators and propose ways to improve the performances of individual monitoring services of Ghana and Gabon if found necessary. The performance indicators assessed included the zero - dose, the minimum detectability and some important reader performance characteristics. These tests were performed using statistical and experimental methods. The overall uncertainty in measurement of the dosimetry systems of Ghana and Gabon for Hp(10) was determined using the IEC technical report TR 62461, and comparisons were carried out with IAEA 99, PTB 99, IEC 1066 and IEC1283 series performance standards. The IEC 62387 standard was used to assess the linearity dependence of the response and the coefficient of variation of the two dosimetry systems. For the Harshaw TLD 6600 system of the dosimetry service of Ghana, the Reference light QC test meets the requirement given in the user manual. For the OSL system microStar of the dosimetry system of Gabon, the three QC tests, DRK count, CAL count and LED count, meet the user manual requirements. However all these tests failed the statistical test that is part of counting statistics. This led to the conclusion that there may be some abnormalities in the counting system, and that the statistical abnormalities suspected have apparently no impact on the results of the reading. It was also concluded that since the DRK count and the CAL count failed the Chi - squared test by very small margin , a Gaussian distribution could still be considered as an approximation of the experimental data distributions of these two QC measurements. The zero dose for the Harshaw 6600 and the microStar system were found to be 0.026 mSv and 0.08 mSv respectively. The monthly lower limit of detection for the TL and OSL systems were found to be 0.08 mSv and 0.05 mSv, respectively. The quarterly recording levels that have been proposed from this work are 0.25 mSv for the Harshaw 6600 system and 0.15 mSv for the microStar system. In spite of some observed abnormal points, the linearity test obtained for the two systems showed that they are globally in accordance with the performance standards tested. The results for the coefficient of variation of the two systems do not meet the IEC 62387 requirement. The results for uncertainty analysis were globally in accordance with the requirements of all the performance standards tested.
Thesis (MPhil) - University of Ghana, 2016